A Cultura Caiçara do Litoral Norte Paulista mostrada na revista Beach&Co Estereótipos do caiçara das cidades de Caraguatatuba, São Sebastião, Ubatuba e Ilhabela em um veículo regional impresso - Guimarães, Bruna Vieira (2014)
The study of the stereotypes that regional magazine Beach&Co about the caiçara, native people who maintain a related culture to the sea in the coastal cities in Caraguatatuba, São Sebastiao, Ubatuba and Ilhabela, on the North Coast os São Paulo. It was applied an methodology that mixture the Cultural Studies based on the books by Douglas Kellner, Stuart Hall and Raymond Williams with Discourse Analysis in the books by Dominique Maingueneau, Eni Orlandi, Patrick Charaudeau and Audre Alberguine. Studies of the Caiçara Culture made by Carlos Diegues, Gioconda Mussolini and Emilio Willems and others; the redefinition the journalism genre Report and the context of the Regional Journalism Magazine. After, the first decade of the magazine Beach&Co, was analyzed in the total of 120 editions published between January 2002 and June 2012, in which were shown the different approaches that the publication did on the caiçara as well as the evolution of the magazine itself in its editorial aspects, commercial and graphic design. Then, 23 reports in the tourism, gastronomy, sports editorials and other related Caiçara Culture were selected and their semantic and evaluative elements of languages were analyzed. It was in the conclusions that the media coverage of Beach&Co prioritizes the areas of tourism and development of São Paulo North and South Coasts, the magazine went through review and dominant schematic view in journalistic production finding market in the specificities of São Paulo Coast; Beach&Co was consolidated at the regional, professionalized, competent and creative journalistic field away from amateurism, the parochialism and simplistic mimicry, dispite of often using the caiçara as adjective of tourist and gastronomic aspects of the North Coast, the magazine worked broadly the symbolic production of the caiçara and portrayed various aspects of Caiçara Culture reinforcing both the power of this regional magazine as feeding back the accents of São Paulo Coast in the other regions of the country.